Intestinal parasitic infections in children from marginalised Roma communities: prevalence and risk factors - Štrkolcová, Gabriela; Fiľakovská Bobáková, Daniela; Kaduková, Michaela; Schreiberová, Andrea; Klein, Daniel; Halán, Miloš; Urbančíková, Ingrid (BMC infectious diseases, 2024)
BACKGROUND: Intestinal parasitic infections remain a significant global health issue, particularly affecting poor and marginalised populations. These infections significantly contribute to children's diseases, malnutrition, poor school performance, cognitive disorders, and future economic losses. This study aimed to explore and compare the occurrence of intestinal parasites in early childhood among the group of infants from the Slovak majority population and from marginalised Roma communities (MRCs). Furthermore, it aimed to explore the health complaints of children with and without intestinal parasitic infection in the past month and assess the effect of various risk factors on the occurrence of intestinal parasitic infection in infants from MRCs. METHODS: We obtained cross-sectional data from mothers and stool samples of their children aged 13-21 months using the first wave of the longitudinal RomaREACH study. A total of 181 stools from infants were analysed: 105 infants from the Slovak majority population and 76 from MRCs. RESULTS: Infants from MRCs are significantly more often infected by Ascaris lumbricoides, Trichuris trichiura and Giardia duodenalis than their better-off peers from the majority population. Infection rates are 30% in infants from MRCs vs. 0% in the majority population (p < 0.001). Single and mixed infections were observed in children from MRCs. Infants with intestinal parasitic infections suffer significantly more often from various health complaints, particularly cough, stomach ache, irritability, and diarrhoea. Within MRCs, the risk of parasitic infections in infants is significantly increased by risk factors such as the absence of flushing toilets in households (OR = 4.17, p < 0.05) and contact with un-dewormed animals (OR = 3.61, p < 0.05). Together with the absence of running water in the household, these three factors combined increase the risk more than ten times (p < 0.01). CONCLUSION: Maintaining hygienic standards in conditions of socioeconomic deprivation in MRCs without running water and sewage in the presence of un-dewormed animals is problematic. These living conditions contribute to the higher prevalence of parasitic infections in children from MRCs, causing various health complaints and thus threatening their health and healthy development.
Keywords: Parasitic infections; Animals; Female; feces; Infant; Prevalence; Feces; Risk factors; ženské pohlaví; průřezové studie; Early childhood; Slovakia; lidé; Intestinal Diseases, Parasitic; Hygienic standards; Risk Factors; prevalence; Cross-Sectional Studies; Male; kojenec; Romové; Marginalised Roma communities; rizikové faktory; Roma; Slovenská republika; parazitární nemoci střev; mužské pohlaví; zvířata; Health complaints; Un-dewormed animals; Humans